Fatigue failure investigation in steel structures with an internal crack - Lim, Alfie Chee Chong (Nanyang Technological University, 2020)
One of the most efficient ways of travelling in Singapore would be the Mass Rapid Transit (MRT). The MRT is responsible for more than 3 million passenger trips daily. [1] In addition to the heavy load of passengers, the high speed of the MRT and the curvature of the track causes rolling contact fatigue (RCF) between the surfaces of the wheel and the surfaces of the rail that are in contact. This paper aims to investigate the crack growth in the White Etching Layer (WEL) through cyclic rolling contact. The study will be done by utilising ANSYS Workbench simulation software. To achieve the aim of the study, a model based on the specifications of the SMRT rail tracks will be constructed. Furthermore, different crack configurations will be used to further understand how the position, length and orientation of cracks will affect the rail. The simulations were run under the same constraints of continuous or dynamic and instantaneous or static compressive loading and traction force, the results gathered will then be used to investigate the crack behaviour in the rail.